Pengaruh Kelompok Referensi, Sikap, dan Kepercayaan Terhadap Keputusan Pembelian Pempek Candy Sukamto - Divandra, Marvela; Kardinal, Kardinal (MDP Student Conference, 2025)
This study aims to analyze the influence of reference groups, attitudes, and trust on purchase decisions at Pempek Candy Sukamto. The research method used is quantitative with a descriptive associative approach. Data was collected through questionnaires distributed to 386 respondents, determined using Slovin’s formula. The data analysis technique employed multiple linear regression with the assistance of SPSS 26 software. The results, both partially and simultaneously, indicate that reference groups, attitudes, and trust have a positive and significant influence on purchase decisions.